Synthesis and Crystal Structure of a New Chiral Mononuclear Complex: [Cu(C10H12N2O)2(NO3)2(H2O)] - Dong, Hua-Ze; Bi, Wen-Tao; Wang, Hong-Fang; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A novel chiral mononuclear complex [Cu(C10H12N2O)2(NO3)2(H2O)], where C10H12N2O) is 3-(dimethylamino)-1-(pyridine-4-yl)prop-2-en-1- one, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal structure analysis shows that the copper(II) is a five-coordinated with a chiral space group in a slightly distorted square pyramidal geometry environment. The crystal is monoclinic, space group Cc with unit cell parameters: a = 20.399(2)Å, b = 9.780(1)Å, c = 13.537(2)Å, α = 90º, β = 116.270(2)º, γ = 90º, V = 2421.8(5) Å3, Z = 4, Mr = 558, Dc = 1.531 Mg/cm3, μ = 0.964 mm-1, F(000) = 1156, Flack x = 0.39(2), T = 291(2) K, R = 0.0561, wR = 0.0979 for 3513 reflections with I > 2σ(I).